Avaliação do sistema de gestão ambiental de um empresa de energia elétrica de grande porte localizada no município de Eusébio-CE - Silva, Demaira Henrique da (2024)
Our planet earth needs care, and in our current society there is a conflict between economic development and environmental preservation in which we can say that consumerism is increasingly exacerbated. This reaffirms the need for cooperation between society, companies and the State, and companies play a large part of the role of multiplier of sustainable development and guarantee of environmental sustainability. The present study sought to evaluate the environmental management system in accordance with the ISO 14001:2015 standard, of a large electric power company, located in the municipality Eusébio-CE, with the intention of proposing improvements and advances for the company's environmental management. The methodology used to evaluate the EMS was the development of checklists based on the requirements of NBR ISO 14001:2015, license conditions and main legislation. Through the application of the checklists, it was possible to raise several aspects in which the company could improve its EMS, including implementing actions with its service providers, developing a more accurate methodology for the field teams and proposing more effective methodologies for the reuse of rainwater. It was also found that 95% of the waste is destined for recycling.It was also found that actions such as environmental training, field audits, and environmental education projects make the company's environmental policy totally directed towards sustainable development. This work is of an applied nature, addressing the qualitative aspects and can also be classified as descriptive research.